10 - GOVERNMENT RESPONSE TO ECONOMIC CRISIS: Text of the Budget Speech 1984 - Journal System, (Africa Development, 1984)
The Head of State Major General Muhammadu BUHARI as reported in the National Concord of May 10, 11 and 12, 1984